Water vapor corrosion behavior and failure mechanism of plasma sprayed mullite/Lu2Si2O7-Lu2SiO5 coatings. Issue 12 (15th August 2018) - Hu, Xunxun; Xu, Fangfang; Li, Kunwei; Jin, Gen; Xu, Yue; Zhao, Xinqing
Abstract: A new coating with mullite as the inner layer and Lu2 Si2 O7 -Lu2 SiO5 (lutetium disilicate-lutetium monosilicate, LuDS-LuMS) composite as the top layer was designed and fabricated on the surface of porous SiC substrate by atmospheric plasma spraying (APS). The microstructure evolution, phase transformation, inter-diffusion and failure mechanism of the coated samples during steam cycling at 1450 °C were systemically investigated. The results indicated that the coated samples maintain weight gain and the average weight gain rate is 1.12 × 10 −1 mg/cm 2 h. The thermal expansion coefficient (CTE) mismatches between the coating and the substrate as well as between the two ceramic layers have produced a thermal mismatch stress. In addition, the chemical reaction induced the sintering of LuDS-LuMS layer, the amorphous-crystalline phase transformation and the transformation between LuDS and LuMS phases could result in aging stress. With the accumulation of thermal mismatch stress and aging stress, the through and horizontal cracks have appeared in the coating, leading to the coating failure.